Розвиток готельно-ресторанного бізнесу в сучасних умовах - Дочинець, Інга Вікторівна (My University, 2024)
Охарактеризовано роботу закладів готельно-ресторанного господарства в різних регіонах України, які відкрились після повномасштабного вторгнення; наведено приклади нових закладів готельно-ресторанного господарства, які здолавши ризики поволі відкриваються, роблячи акцент на оригінальності та доступності для споживачів The work of hotel and restaurant establishments in different regions of Ukraine, which opened after a full-scale invasion, is characterized; examples of new establishments in the hotel and restaurant industry are given, which, after overcoming the risks, are slowly opening, emphasizing originality and accessibility for consumers
Keywords: кафедра готельно-ресторанної справи; культура харчування; сфера гостинності; туризм; food culture; hospitality; development; tourism; tourism